The Fate of the Brazilian Collection of the State Zoological Museum in Warsaw Before and During the Second World War (1939–1945) - Mierzwa-Szymkowiak, Dominika; Borecki, Higor Gabriel; Costa Straube, Fernando; Gondek, Mário José; Cegliński, Arkadiusz (Faces of War, 2025)
Before the Second World War, the State Zoological Museum in Warsaw was a dynamically functioning research institution, characterised by its rapidly growing collections of contemporary animals for scientific, educational and exhibition purposes. The specimens were mainly collected during expeditions organised by the museum’s staff. One of the explorers was Tadeusz Chrostowski (1878–1923), an ornithologist and head of the Neotropical Birds Department of the Museum. The naturalist organised three expeditions to Brazil in 1910–1911, 1913–1915 and 1921–1923. He explored areas of the state of Paraná that were considered the least explored. Chrostowski’s last journey, known as the Polish Zoological Expedition, received the most attention in scientific and social circles. It was the leading overseas scientific expedition organised by the newly revived Polish state. In addition to Chrostowski, the research team included the entomologist Tadeusz Jaczewski (1899–1974) and the taxidermist Stanisław Borecki (1888–1968). The team aimed to study the fauna of southern and central Paraná, specifically in areas with araucaria humid forests inhabited by Polish colonies, subtropical forests, and along the rivers Ivaí, Paraná and Iguaçu. A collection of over 22,000 zoological specimens was one of the outcomes of the fieldwork. The material included many species of birds first found in the Paraná. The collection was taken to Warsaw in 1924 and was available to researchers in the museum until 1939. The Second World War was a tragic event in the history of the institution. Not only did it interrupt scientific and research activities, but it also contributed to the loss of part of the collection. Among the museum’s war losses were more than 2 million animal specimens, including more than 20,000 of Chrostowski’s specimens. The collections were destroyed, confiscated and exported and many were dispersed. Research into the history of Chrostowski’s collection aims to reconstruct and describe it, as well as to spread knowledge of the wartime losses suffered by the State Zoological Museum during the Second World War.